Chronic urticaria in the real-life clinical practice setting in Portugal: 2-years results from the non-interventional multicenter AWARE study - Costa, Célia (2022)
Introduction: Information regarding chronic urticaria patients in the real-world setting is scarce. This analysis reports the two-year results of Portuguese patients included in the AWARE study.Material and Methods: Non-interventional cohort study. Adult patients with a diagnosis of chronic urticaria with symptoms for at least two months, refractory to H1-antihistamines, consulting one of the 10 participating urticaria centers throughout Portugal, from the 31st October 2014 to 31st July 2015, have been included in the study. Clinical parameters, medicines taken for urticaria symptom relief, weekly urticaria activity score, and dermatology quality of life index have been collected throughout the two years of the study.Results: Seventy-six patients were enrolled in the study. Results showed that the proportion of patients with omalizumab therapy almost duplicated after two years of the AWARE study, which was accompanied by the decrease of medical resources use and absenteeism. Moreover, urticaria severity and impact on quality of life both decreased after one year and continued to decrease at two years, although decreased severity was significant at both time points and quality of life was only significant at two years. At the end of two years, 79.0% of patients had their disease controlled compared to 29.3% at baseline (p < 0.001).Discussion: At the end of the AWARE study a significant proportion of patients had their disease controlled allowing for decreased use of medical resources.Conclusion: Chronic urticaria still has a significant impact on quality of life and therefore there is opportunity for further therapy optimization.